2020
DOI: 10.1186/s12889-020-09065-x
|View full text |Cite
|
Sign up to set email alerts
|

The differential effect of maternal dietary patterns on quantiles of Birthweight

Abstract: Background Maternal dietary habits during pregnancy are considered essential for development and growth of the fetus as well as maternal health. It has an effect on the birthweight of infants. However, little is known about the effect of dietary patterns on birthweight in urban South Africa. This study aimed to investigate differential effect of dietary patterns of pregnant women on quantiles of birthweight. Methods Data for the study were obtained from a Mother and Child in the Environment birth cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…After the removal of duplicates, 4.918 article titles and abstracts were screened. Of these, 151 full-text articles were further assessed for eligibility and, finally, 61 studies [ 4 , 18 , 19 , 20 , 21 , 22 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ,…”
Section: Resultsmentioning
confidence: 99%
“…After the removal of duplicates, 4.918 article titles and abstracts were screened. Of these, 151 full-text articles were further assessed for eligibility and, finally, 61 studies [ 4 , 18 , 19 , 20 , 21 , 22 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ,…”
Section: Resultsmentioning
confidence: 99%
“…Exploratory factor analysis is a statistical method that allows for deriving empirical dietary patterns and has been extensively employed as a tool for the assessment of maternal diet during pregnancy [ 7 , 23 , 24 , 26 , 30 , 31 , 32 , 33 ]. This data-driven technique reduces the dimensionality of dietary variables to a few components [ 34 ]; nevertheless, the natural interpretability of the derived factors depends on several subjective and arbitrary decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are not easily compared to other studies due to differences in analytical methods. However, a study from South Africa found that dietary patterns affected birth weight in different quantiles using quantile regression [ 6 ]. Based on previous findings from others, our results are somewhat unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that frequency of milk intake was associated with birth weight [ 16 ]. As dietary patterns using factor analysis have shown associations with birth size, this could perhaps be another useful method in this setting [ 6 ]. Thirdly, a minimum consumption amount of a food item was not required for it to be included in the DDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation